Social conflicts in the selected poems of Resurreccion Hidalgo. - Vila, Jorgen N. (2006)
This study aims to determine the social conflicts reflected in the poems of Hidalgo and to analyze the social conflicts reflected in each poem.
Undergraduate thesis-BA Literature-Management, UP Visayas, Miag-ao, Iloilo
Keywords: Hidalgo, Resurreccion; Hiligaynon poetry -- History and criticism